Agricultural transformation in the savannah: Perspectives from the village - Johnson, Michael E.; Houssou, Nazaire; Kolavalli, Shashidhara; Hazell, Peter B. R. (International Food Policy Research Institute, 2019)
Most of the evidence presented in this book about changes in the agricultural sector draws on secondary data and nationally representative household surveys like the GLSS. This chapter seeks to ground the truth of some of the key findings by providing village and farmer perspectives on important changes that have impacted on their livelihoods since the 1980s, and how they have adapted their farming systems and practices. The chapter also addresses several key questions. What were the key factors driving farmers’ adaptation decisions, including the roles of changes in population density and the availability of additional land for cultivation, improved access to markets, changing market demands, increased competition for labor from the rural nonfarm economy, and higher wages? Why, despite continuing rural population growth, have farmers generally chosen to adopt technologies and farming practices that increase labor productivity relative to land productivity? Finally, what happens once options for bringing more land into production become exhausted?